Long-Term Safety and Efficacy of Lenabasum, a Cannabinoid Receptor Type 2 Agonist, in Patients with Dermatomyositis with Refractory Skin Disease: Follow-Up Data from a 3-Year Open-Label Extension Study - Caroline J. Stone; Geeta Ahuja; Lais Lopes Almeida Gomes; Joy Poroye; Daniella Forman Faden; Lillian Xie; Rui Feng; Barbara White; Victoria P. Werth (JID Innovations)
Background: Dermatomyositis (DM) is a rare autoimmune condition involving skin manifestations often resistant to standard treatments such as immunosuppressants and antimalarials. Biopsies show elevated inflammatory cells such as CD4+ T cells, dendritic cells, and cytokines. Lenabasum, a selective cannabinoid receptor 2 agonist, has demonstrated significant benefits in treating autoimmune skin diseases. Objectives: This study utilizes data from the open-label extension (OLE) phase of the lenabasum phase 2 trial and additional post-OLE follow-up data. Key aims include evaluating the drug’s long-term effectiveness and assessing disease manifestation recurrence. Methods: The phase 2 lenabasum trial enrolled patients with treatment-resistant, skin-predominant DM. The OLE consisted of a 3-year period during which 20 patients were on the drug for the entire duration, with assessments every 8 weeks to evaluate drug safety and efficacy. Subsequently, a follow-up retrospective chart review was performed on patients who completed the OLE as well as on control subjects with DM who did not participate in the lenabasum trial. Results: By week 68, patients exhibited reductions in Cutaneous Dermatomyositis Disease Area and Severity Index activity score (−21.8), Patient Skin Activity Visual Analog Scale (−3.0), and Skindex-29 (−28.0) from OLE baseline. After OLE, 58.3% maintained stable disease, significantly higher than controls (P = .035), with 41.7% not experiencing flares compared with 91.6% of controls. In addition, 50% of patients reported sustained pruritus improvement. Conclusions: Data from OLE and subsequent follow-up periods demonstrate lenabasum’s efficacy in maintaining disease stability, reducing flares, and improving DM symptoms, suggesting that it is a promising option for patients with treatment-resistant skin-predominant DM. Trial Registration: This study was registered at clinicaltrials.gov, with NCT02466243. Study registration was first submitted on June 2, 2015.